Modelling of fresh properties and strength activity index with microstructure characterisation of ternary cement incorporating waste glass and granulated blast furnace slag - Salah Eddine Daguiani; Oussama Kessal; Abdelouahed Kriker; Abdessamed Mokhtari (Fracture and Structural Integrity)
Research in innovative construction materials has focused on utilising supplementary materials in cementitious composites to promote sustainable development and reduce CO2 emissions. Within this context, this study aims to investigate the fresh properties and assess the pozzolanic activity of ternary blended cement by incorporating two industrial waste materials, namely waste glass (WG) and granulated blast furnace slag (GBS), as cement replacements up to 30%. A mixture design approach was employed for composition optimisation, and mathematical models were implemented to achieve this. XRD and SEM/EDS analyses were conducted to examine the structure and composition of the cementitious matrix. The results indicate that the setting time was prolonged compared to the reference mixture. Furthermore, based on the results of the SAI (Strength Activity Index) test, an acceptable level of strength development was demonstrated, confirming that WG and GBS possess the potential to replace cement while meeting the minimum strength requirements outlined in the specifications. Microstructure analyses revealed good adhesion between WGP, GGBS, and the cementitious binder. This research contributes to the development of eco-efficient binders that exhibit increased cement replacement ratios and qualities comparable to, or even superior to, traditional cement systems.